Study the Use of Paragraph Writing Principles in Lao Folk Tales - PHOLLUXA, Khamphuy; SEEBOUNHEUANG, Outhay; VONHPHACHANH, Phitsaphong; SOUTTHIXAY, Souksada; VILAIVONE , Chab (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research focuses on the application of paragraph-writing principles in Lao folktales, with the objective of analyzing the narrative structure of the tale Kampa Kaap Lang according to these principles and identifying the key idea sentences in each paragraph. The findings reveal that Kampa Kaap Lang is an extended narrative consisting of 87 paragraphs. The organization of the story, based on paragraph-writing principles, involves seven steps: (1) reading the entire story to understand its full content; (2) dividing the story into major sections; (3) breaking each section into smaller units based on events and character actions, thereby forming paragraphs; (4) combining narrative units according to the sequence of events and character actions to create coherent paragraphs; (5) removing unnecessary introductory or redundant words and converting poetic expressions into prose while retaining the characters’ original poetic dialogue in quotation marks when necessary; (6) arranging the narrative into paragraphs based on the principle that each paragraph contains one main idea sentence; and (7) using Lao punctuation correctly within each paragraph. Regarding the identification of key idea sentences in Kampa Kaap Lang, the study confirms the presence of 87 paragraphs, each containing one main idea sentence, resulting in a total of 87 key idea sentences. These sentences convey moral teachings essential to life, expressed through a tone of faithful, gentle, and tender love that reflects core Lao cultural values.